UVEO MENINGEAL SYNDROME (HARADA) DISEASE - Khan, Jaffar; Aftab, M. (Journal of Ayub Medical College Abbottabad, 1989)
Abstract: A case of bilateral exudative retinal detachment in a young girl of 13 years is reported. She had fever, headache and vomiting prior to ocular symptoms. On examination she had premature greying of hair and ophthalmoscopy showed bilateral hazy vitreous, swollen optic discs and exudative retinal detachment. Therefore, a diagnosis of Harada disease was made. She was treated with high doses of steroids to which she responded very well.